The content validity of the Behaviour Support Plan Quality Evaluation tool (BSP‐QEII) and its potential application in accommodation and day‐support services for adults with intellectual disability. (30th July 2012) - McVilly, K.; Webber, L.; Sharp, G.; Paris, M.
Abstract Background The quality of support provided to people with disability who show challenging behaviour could be influenced by the quality of the behaviour support plans (BSPs) on which staff rely for direction. This study investigated the content validity of the Behaviour Support Plan Quality Evaluation tool (BSP‐QEII), originally developed to guide the development of BSPs for children in school settings, and evaluated its application for use in accommodation and day‐support services for adults with intellectual disability. Method A three‐round Delphi study involving a purposive sample of experienced behaviour support practitioners (n = 30) was conducted over an 8‐week period. The analyses included deductive content analysis and descriptive statistics. Results The 12 quality domains of the BSP‐QEII were affirmed as valid for application in adult accommodation and day‐support service settings. Two additional quality domains were suggested, relating to the provision of detailed background on the client and the need for plans to reflect contemporary service philosophy. Furthermore, the results suggest that some issues previously identified in the literature as being important for inclusion in BSPs might not currently be a priority for practitioners. These included: the importance of specifying replacement or alternative behaviours to be taught, descriptions of teaching strategies to be used, reinforcers, and the specification of objective goals against which to evaluate the success of the intervention programme. Conclusions The BSP‐QEII provides a potentially useful framework to guide and evaluate the development of BSPs in services for adults with intellectual disability. Further research is warranted to investigate why practitioners are potentially giving greater attention to some areas of intervention practice than others, even where research has demonstrated these others areas of practice could be important to achieving quality outcomes.